Confirmatory factor analysis and measurement invariance of the Depression, Anxiety, and Stress Scale (DASS-21) among Pakistani young adults - S. M. A. Kazmi; C. A. Lewis (European Psychiatry, 2024)
Introduction The Depression, Anxiety and Stress Scale (DASS-21) is recognized as being a widely used measure for the assessment of negative emotional states. While the DASS-21 has been widely used for assessing mental health in Pakistan, limited research has been done regarding its factor structure and measurement invariance.